هل هو أمر بالقضاء أم لا؟ - و يصل، أروجوف; Orujovi, Veisal (Fatih Sultan Mehmet Vakıf Üniversitesi, 2024)
الحمد هَّل ربِّ العالمين والصلاة والس لم على سيِّدنا محمَّد وعلى آله وصحبه وسلَّم، ا ل وبعد، تطرَّقت في هذا البحث لتعريفات الأداء والقضاء، فهذه التعريفات ليست محلَّ اتِّفاق عند الأصوليِّين كونها من أقسام الحكم الوضعي أو لواحقَ وتوابعَ له، إ اَّ أنَّها في جميع ل التقديرات لا يُمكن أن تنفكَّ عن الحكم الوضعي، فعاملُ الوقت فيها هو المؤثِّر الرئيس في هذه التعريفات؛ ذلك أنَّ الوقت سبب للأداء وخروجَه سببٌ للقضاء، والسبب من أقسام الحكم الوضعي المتَّفق عليها عند الأصوليِّين، كما أنَّ هناك العديد من المسائل الأصوليَّة المتعلِّقة بمصطلح الأداء والقضاء، ومن أهمِّها: مسألةُ الأمر بالأداء هل هو أمر بالقضاء أو لا؟ وهي المسألة التي استعرضتها في بحثي هذا، وذكرت أقوال العلماء فيها مع أدلَّتهم، ومع بيان آثار اخت لف العلماء فيها على الفروع الفقهيَّة.

Hamd, âlemlerin Rabbi olan Allah’a mahsustur. Salât ve selâm, Efendimiz Muhammed’e, âline ve ashabına olsun. Bu araştırmada edâ ve kazâ tanımlarına değindim. Bu tanımlar, usûl âlimleri arasında üzerinde ittifak edilen konular değildir. Çünkü bunlar, ya vaz’î hükmün kısımlarından ya da ona bağlı unsurlardandır. Ancak her hâlükârda vaz’î hükümden bağımsız düşünülemezler. Zira bu tanımlarda belirleyici olan temel unsur, zamandır. Çünkü zaman, edânın sebebidir ve zamanın çıkması da kazânın sebebidir. Sebep ise usûl âlimleri arasında ittifak edilen vaz’î hüküm kısımlarındandır. Ayrıca edâ ve kazâ terimleriyle ilgili birçok usûlî mesele bulunmaktadır. Bunlardan en önemlisi de “Edâ emri, kazâ emri midir, değil midir?” meselesidir. Araştırmamda bu meseleye yer verdim; âlimlerin bu konudaki görüşlerini, delilleriyle birlikte açıkladım ve âlimler arasındaki görüş ayrılığının fıkhî meseleler üzerindeki etkilerini de belirttim.

Praise belongs to Allah, the Lord of the worlds. May peace and blessings be upon our Master Muhammad, his family, and his companions. In this research, I addressed the definitions of performance (edâ) and make-up (kazâ). These definitions are not matters of consensus among scholars of Islamic legal theory (usûl). This is because they are either categories of circumstantial ruling (vaz'î) or elements dependent on it. However, in any case, they cannot be considered independent of circumstantial ruling. The determining factor in these definitions is time. Time is the cause of performance (edâ), and the passing of time is the cause of make-up (kazâ). Cause is one of the categories of circumstantial ruling agreed upon among scholars of legal theory. Additionally, there are many theoretical issues related to the terms edâ and kazâ. The most important of these is the question "Is the command for performance the same as the command for make-up or not?" In my research, I included this issue, explained the scholars' views along with their evidence, and noted the effects of scholarly disagreement on jurisprudential matters.
Edâ Emri, Kazâ Emri Midir, Değil midir?
Is the Command for Performance (Edâ) the Same as the Command for Make-Up (Kazâ) or not?
Keywords: مباحث الأداء; أنواع القضاء; تسميات القضاء; أقسام العبادات; Edâ meseleleri; Kazâ Çeşitleri; Kazâ Terimleri; İbadet Türleri; Performance Issues; Types of Make-Up; Make-Up Terms; Types of Worship